Determinants of Residential Electricity Demand: Empirical Evidence from Pakistan - Muhammad Hassan, Akhtar; Nasir, Iqbal; Bilal, Tariq; Rossazana Ab-Rahim, Ab-Rahim (HRMARS, 2020)
This study is based on the estimation of residential demand of electricity for Pakistan with major focus on the income elasticities and the luxury appliances impact over the demand. The monthly electricity unit consumption is used as dependent variable that is constructed through backward induction method from monthly electricity expenditure that help to find clear dimensions of the demand. For estimation of demand Two Stage Least Square method of estimation has used with the five explanatory variables; household monthly income, household size, dwelling size, appliances and luxury appliances. The empirical analysis is conducted by using Two Stage Least Square methods. The empirical findings represent the positive significant income elasticities that are almost the same across the different income groups in various regions. The household demand for electricity has strong response to the luxury appliances. The household size revealed negative significant response to the residential demand for electricity. The dwelling size and appliances have shown positive significant or insignificant impact over the residential electricity demand.